Identifikasi Tingkat Kerawanan Kebakaran Hutan Lahan Berbasis Model Spasial Multi-Kriteria dengan Teknik Skoring–Overlay di Provinsi Sumatera Selatan: Indonesia - Saputri, Chendrika; Rumaday, Nada Naurah; Darmawan, Yahya; Rahma, Nuzula Elfa; Franchitika, Rizky (Jurnal Sains & Teknologi Lingkungan, 2026)
Forest fires are a major environmental problem in the province of South Sumatra, Indonesia, affecting ecosystems, public health, and the economy. Through scoring and overlay methods, this study was conducted to analyze the potential of forest fires in South Sumatra. This scoring method evaluates forest fire risk factors such as rainfall, soil type, land cover. Data from various sources were collected and processed, including satellite imagery, weather data, and historical fire reports using hotspot data detected by satellite imagery, showing a correlation between the vulnerability of Province South Sumatera to forest and land fires. The results of the assessment analysis were integrated into a geographic information system (GIS) using overlay technology to create a map of forest fire potential. This map identifies areas with high, medium and low fire risk. Based on the research, the likelihood of forest fires is high in some areas of South Sumatra, especially during the dry season. Data analysis showed significant variability in the number of fires from year to year, with 2014, 2019, and 2023 being the highest peak. The objective of this research is to develop a fire susceptibility map based on physical and climatological parameters and to validate the model's accuracy against historical hotspot distributions. This susceptibility map is intended to serve as a spatial instrument for government authorities and stakeholders in designing more precise fire prevention and mitigation strategies based on the intrinsic characteristics of the South Sumatra region.